2001
DOI: 10.1097/00000478-200108000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Cancer Following a Diagnosis of High-Grade Prostatic Intraepithelial Neoplasia on Needle Biopsy

Abstract: Most studies on the risk of cancer after high-grade prostatic intraepithelial neoplasia (PIN) on biopsy have been small (fewer than 100 men), have not analyzed in detail if histologic features can predict cancer, and have not assessed the risk of cancer with multiple repeat biopsies. We analyzed 245 men in whom the only abnormal finding on the initial biopsy was high-grade PIN and who had at least one follow-up biopsy. Repeat biopsy identified cancer in 32.2% of men. If only one follow-up biopsy had been perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(79 citation statements)
references
References 15 publications
4
72
0
3
Order By: Relevance
“…This finding was in consistence with Kronz et al [26] and Schoenfield et al [20] who found cancer of the prostate on the 2 nd biopsy in third of their patients having HGPIN on the 1 st biopsy with higher rate of cancer detection in multifocal than unifocal HGPIN. This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy.…”
Section: Discussionsupporting
confidence: 88%
“…This finding was in consistence with Kronz et al [26] and Schoenfield et al [20] who found cancer of the prostate on the 2 nd biopsy in third of their patients having HGPIN on the 1 st biopsy with higher rate of cancer detection in multifocal than unifocal HGPIN. This indicates that the prostate cancer risk is increased with the increase in the number of specimens found to have HGPIN on the 1 st biopsy.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that cribriform PIN conveys an increased risk of developing into invasive cancer compared to other types of PIN. 16,17 Others have failed to confirm this finding. 18 The split opinion on the prognostic impact of PIN architecture may explain that only 19% of respondents specified architectural patterns in needle biopsy reports.…”
Section: Discussionmentioning
confidence: 98%
“…Initially, a high risk was reported, usually in the interval of 30-40%. 17,19 16,18,20 The decreased predictive value for cancer may be explained by an increasing number of cores in each biopsy session. When no cancer is found in multiple biopsy cores, the risk of missing an invasive cancer is evidently lower than when a limited number of cores are taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, resolving the importance of these disparate events requires attention to confounding variables such as age and equally important, the intrinsic sampling variation across different tissue sections, each with presumably different amounts of epithelium. 14 Numerous examples in the literature attest to the importance of ascertaining precursor frequency or size as a surrogate for cancer risk, such as in the colon, pancreas and prostate, [15][16][17][18][19][20][21][22][23][24] These organs house early epithelial changes that are not unlike the SCOUTs described in the fallopian tube. As high precursor frequencies could signal an acquired or underlying familial tendency for cancer development, precise quantification of the epithelial perimeter at risk is paramount.…”
mentioning
confidence: 99%